2021
DOI: 10.1177/23247096211053709
|View full text |Cite
|
Sign up to set email alerts
|

Heart of the Matter: Syncope as a Rare Presentation of Lung Cancer Invading the Heart

Abstract: Syncope is common, affecting approximately 1 million Americans every year. Although multiple pathophysiological mechanisms regarding its etiology have been documented, neurocardiogenic or vasovagal syncope is the most common cause of these episodes. Other less appreciated etiologies include various cardiac abnormalities in which a structural, electrical, or obstructive disturbance leads to a temporary reduction in blood flow to the brain, resulting in transient loss of consciousness. Cardiac malignancies, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…An interruption in cardiac function can cause irreversible impairments, such as brain injury, heart failure, stroke, or even sudden cardiac death [ 5 ]. Malignancies have had a significant impact on the cardiovascular system; for example, lung cancer has been shown to disrupt the conduction system [ 6 ]. Similarly, several case studies in the past have demonstrated fluctuations in the cardiac functions of patients with carcinoma of the pancreas [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An interruption in cardiac function can cause irreversible impairments, such as brain injury, heart failure, stroke, or even sudden cardiac death [ 5 ]. Malignancies have had a significant impact on the cardiovascular system; for example, lung cancer has been shown to disrupt the conduction system [ 6 ]. Similarly, several case studies in the past have demonstrated fluctuations in the cardiac functions of patients with carcinoma of the pancreas [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%